1995
DOI: 10.1111/j.1365-2672.1995.tb03144.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Listeria in dry fermented sausages by the bacteriocinogenic Lactobacillus sake CTC494

Abstract: Lactobacillus sake CTC494 isolated from a naturally fermented sausage, produced an antibacterial agent active against selected strains of Listeria monocytogenes and L. innocua. The agent was bacteriolytic against L. monocytogenes and sensitive to proteolytic enzymes; it was identified as a bacteriocin and was designated as sakacin K. The ability of Lact. sake CTC494 to inhibit the growth of listeria, compared to a bacteriocinogenic negative control strain, was examined in a model sausage system and in dry ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(94 citation statements)
references
References 35 publications
3
86
0
5
Order By: Relevance
“…Many problematic factors are known to be associated with the food matrix and bacteriocins (Schillinger and Lücke, 1991;Degnan and Luchansky, 1992;Crandall and Montville, 1993;Vandenbergh, 1993;Abee et al, 1995;Hugas et al 1995;Holzapfel et al, 1995;Leisner et al, 1996;Stiles, 1996), and this experiment showed how difficult it may be for a biopreservative to occupy vital niches in a product. Fears have been expressed towards clean room production lowering the natural contaminant level in the product and leading perhaps to more vulnerable products.…”
Section: Resultsmentioning
confidence: 73%
“…Many problematic factors are known to be associated with the food matrix and bacteriocins (Schillinger and Lücke, 1991;Degnan and Luchansky, 1992;Crandall and Montville, 1993;Vandenbergh, 1993;Abee et al, 1995;Hugas et al 1995;Holzapfel et al, 1995;Leisner et al, 1996;Stiles, 1996), and this experiment showed how difficult it may be for a biopreservative to occupy vital niches in a product. Fears have been expressed towards clean room production lowering the natural contaminant level in the product and leading perhaps to more vulnerable products.…”
Section: Resultsmentioning
confidence: 73%
“…Inhibition of spoilage of fresh meat by bacteriocinogenic Lactobacillus sakei (Lb. sakei) CTC 494 (sakacin K-producing) together with MAP has been reported (26). Aymerich et al (4) characterized Lb.…”
Section: Introductionmentioning
confidence: 99%
“…Literature data indicate that different strains of Lb. sakei isolated from meat and meat products have the ability to produce secondary metabolic substances -bacteriocines with a strong antilisterial activity [28][29][30].…”
Section: Discussionmentioning
confidence: 99%